The Analysis of Nurses’ Positive Deviance Behaviours as a Measure in Preventing the Transmission of Healthcare-Associated Infections (HAIs) at M. Djamil Hospital, Padang, West Sumatera - Esthika Ariany Maisa; Yulastri Arif; wawan Wahyudi (Elevate, 2018)
Purpose: To explore the nurses’ positive deviance behaviors as an effort to provide solutions in preventing and controlling infections in the hospital. Method: This is a qualitative research using grounded theory approach. Thirteen nurses from Dr.M.Djamil hospital were selected based on theoretical sampling in order to develop theory as it appears. Nurses were interviewed from June to September 2014. Interviews were thematically analyzed using techniques of grounded theory to then generate a theory from themes formed. Findings: The modes of positive deviance behavior identified were practicing hand hygiene beyond the standards (bringing handsanitizer from home), applying nursing art in wound care practice, placing patients with MRSA infections at the corner side, giving a red mark on a MRSA patient’s bed for easy identification by nurses, changing clothes and shoes in hospital, reducing hooks on the wall, and cleaning the ward on scheduled days. Conclusion: The study shows that nurses have a number of positive deviance behaviors to prevent infection transmission in the wards. It is sugested that the hospital management and nursing managers adopt some of the uncommon solution highlighted by the nurses to solve the HAIs problems in the hospital.0